Theoretical design of ultracompact three-dimensional isotropic two-photon 4Pi STED microscopy based on multifunctional metalenses focusing system. (28th July 2022) - Li, Yang; Zhao, Shihu; Ju, Dandan; Luo, Mingyan; Xiu, Dongming; Liu, Shujing; Shen, Hui
Abstract: 4Pi stimulated emission depletion (STED) microscopy shows outstanding three-dimensional (3D) isotropic super-resolution imaging performance. However, this technology is still difficult for achieving long-term studying of the synapses that are deeply embedded inside brain tissue. Metalens, which can realize arbitrary nanoscale amplitude, phase, and polarization modulations, is a very useful tool to solve this limitation. In this paper, an ultracompact two-photon 4Pi STED microscopy involved two multifunctional metalenses patterned on the two fiber facets respectively for focusing the excitation and depletion laser beams to the same position was proposed to realize the 3D isotropic super-resolution imaging. The designed complementary structure of two metalenses and the optimized pupil ratio β assured the symmetry of the STED spot. Furthermore, the isotropic super-resolution of 27 nm was theoretically implemented based on the two-photon STED theoretical model. Our approach will greatly increase the viability of the 3D super-resolution morphological imaging in the deep brain.